2018
DOI: 10.1177/0950017018762276
|View full text |Cite
|
Sign up to set email alerts
|

Class and Precarity: An Unhappy Coupling in China’s Working Class Formation

Abstract: In refuting Guy Standing's precariat as a class, we highlight that employment situation, worker identity and legal rights are mistakenly taken as theoretical components of class formation. Returning to theories of class we use Dahrendorf's reading of Marx where three components of classes, the objective, the subjective and political struggle, are used to define the current formation of the working class in China. Class is not defined by status, identity or legal rights, but location in the sphere of production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 49 publications
1
36
0
1
Order By: Relevance
“…Although our study could not prove the magic power of work experiences during schooling, it did confirm our prediction that students from poor families who work part-time are more prosocial, which possibly generates mutual support when encountering problems and difficulties. Based on qualitative research (Smith & Pun, 2018), students of lower SES were found to be prosocial and cooperative such as sharing job information and tips for surviving in labor markets not only as individuals but also as peer groups. Lacking resources did not necessarily accelerate competition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our study could not prove the magic power of work experiences during schooling, it did confirm our prediction that students from poor families who work part-time are more prosocial, which possibly generates mutual support when encountering problems and difficulties. Based on qualitative research (Smith & Pun, 2018), students of lower SES were found to be prosocial and cooperative such as sharing job information and tips for surviving in labor markets not only as individuals but also as peer groups. Lacking resources did not necessarily accelerate competition.…”
Section: Discussionmentioning
confidence: 99%
“…Probably because working-class students realized that exploitation at work is not uncommon (e.g., Brown & deCant, 2014; Pun & Koo, 2019), they learnt from their work experience that they must protect their basic labor rights so they were eager to acquire knowledge of China’s Labor Contract Law. Students shared labor rights knowledge that they learnt at school and sometimes discussed it vigorously among their peers when facing wage arrears or work injuries (Smith & Pun, 2018). Social connection and willingness to help are of particular importance to these working-class students who learnt how to cope with difficulties that frequently happen.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, however, the power they possess at the point of production creates the objective potential for a powerful working-class movement. Smith and Pun (2018) criticize the use of legal status as a means of defining a class group, instead explicitly understanding precarization as process. Nonetheless, in order to get to grips with such processes, it is imperative to take contractual differentiation or migrant divisions of labour seriously.…”
Section: Drivers and Patterns Of Precarization And The Role Of The Smentioning
confidence: 99%
“…It is important to note, however, that this kind of insight is lost when ‘precarity’ is used over-extensively as the defining characteristic of a class. For this reason, Smith and Pun (2018) forcefully attack analyses of ‘the precariat’ which assign them the role of victims, through a focus on the emerging Chinese working class. From a Marxist perspective, they claim that insecurity and legal discrimination based on the household registration system pose a severe problem for Chinese workers.…”
Section: Drivers and Patterns Of Precarization And The Role Of The Smentioning
confidence: 99%
“…The recent publication in this journal of a special issue on precarity represents an important step in the ongoing debate on the concept of precarity and on the forms of organization and resistance of workers in precarious conditions. Most importantly, as argued by the editors and a number of articles in the special issue, there is a need to go beyond the overstretching of ‘precarity’ as a concept, and to look at precarity as a process in order to understand how structural contextual variations impact upon subjective experiences (Alberti et al, 2018; Choi, 2018; Moore and Newsome, 2018; Smith and Ngai, 2018). Attention must be paid to the role of different state and capital regulations in reconfiguring precarity and disempowering workers.…”
Section: Introductionmentioning
confidence: 99%